P632 Etrasimod induction therapy in moderately to severely active Crohn's disease: results from a phase 2, randomised, double-blind substudy. (30th January 2023) - D'Haens, G; Dubinsky, M C; Peyrin-Biroulet, L; Danese, S; Sands, B E; Wolf, D C; Yarur, A; Chiorean, M; Dray, D; Modesto, I; Tan, H; Gu, G; et al.
Abstract: Background: Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development to treat immune-mediated inflammatory disorders. CULTIVATE (NCT04173273) is a seamless phase 2/3 trial comprising 5 substudies designed to evaluate the efficacy, safety, and tolerability of etrasimod in subjects with moderately to severely active Crohn's disease (CD). Here, we report the induction data from the first substudy (Substudy A). Methods: Substudy A was a phase 2, randomised, double-blind study using a 14-week induction period followed by a 52-week extension period. Adults (18-80 years) with moderately to severely active CD and an inadequate response, loss of response to, or intolerance to ≥1 conventional or advanced treatments for CD were randomised 1:1 to once-daily etrasimod 2 mg or 3 mg. Subjects were stratified by baseline biologic failure status and oral corticosteroid use. The primary efficacy endpoint was achievement of endoscopic response (defined as endoscopic remission [SES-CD ≤4 and ≥2-point reduction from baseline with no subscore >1] or ≥50% decrease in SES-CD score) at week 14. Secondary/exploratory endpoints included achievement of endoscopic remission, clinical remission (CDAI <150), and IBDQ remission (IBDQ ≥170) at week 14. Outcomes were analysed in the Full Analysis Set (all randomised subjects treated with ≥1 dose) using NRI or observed data. Results: Of 83 subjects randomised to etrasimod 2 mg or 3 mg, respectively, 32/42 (76.2%) and 36/41 (87.8%) completed week 14 (Table 1). Overall, 21.4% and 9.8% of subjects in the 2-mg and 3-mg groups, respectively, achieved the primary endpoint of endoscopic response, 14.3% and 7.3% achieved endoscopic remission, 31.0% and 43.9% achieved clinical remission, and 33.3% and 40.0% achieved IBDQ remission at week 14 (Figure 1). Most treatment-emergent AEs were mild or moderate, with more AEs reported in the 3-mg vs 2-mg group. The incidence of serious AEs (4.8% and 2.4%) and AEs leading to discontinuation (4.8% and 7.3%) was low in the 2-mg and 3-mg groups, respectively (Table 2). Two subjects in the 3-mg group experienced second degree atrioventricular block type 1 TEAEs (during 2-mg titration). Conclusion: Data from this substudy of subjects with moderately to severely active CD suggest endoscopic and clinical improvement with both etrasimod 2 mg and 3 mg. However, the small sample size and lack of placebo arm limit the ability to draw conclusions about efficacy including comparison between the 2-mg vs 3-mg groups. Both doses were well tolerated and safety was consistent with other etrasimod clinical programmes. Data from the extension phase of Substudy A and the placebo-controlled, dose-ranging phase 2b Substudy 1 are forthcoming.